Did labour market concentration lower wages growth pre-COVID? - Jonathan Hambur (The Australian Government, The Treasury, 2023)
Wages growth in Australia was lower than expected prior to COVID-19 based on historical determinants. One possible explanation for this is that employment had become more concentrated among a small number of large employers. This reduced outside options for workers and lowered their bargaining power and wages. This paper examines concentration in Australian labour markets and its impacts on wages using a large and representative database derived from administrative tax data. Labour markets have not, on average, become more concentrated over time. However, the impact of any given level of concentration has increased since the 2010s. This may help explain surprisingly low wages growth pre-COVID, despite labour market concentration having remained constant. Simple back-of-the-envelope estimates suggest that the greater impact of concentration may have lowered wages by a little under 1 per cent on average between 2011 and 2015. Declining firm entry and dynamism appear to have contributed to the increased impact of concentration, and lower wages growth, by lowering competition for labour among incumbent firms. Declining union coverage and occupational mobility may also have played a role, but declining firm entry appears to have been the main driver.
Keywords: C23; C55; D22; D43; E24; J30; 330; wages; market power; labour markets; concentration